LuxS in Lactobacillus plantarum SS-128 Improves the Texture of Refrigerated Litopenaeus vannamei: Mechanism Exploration Using a Proteomics Approach - Li, Yuan; Qian, Yilin; Lou, Xiaowei; Hu, Zhiheng; Hu, Yaqin; Zeng, Mingyong; Liu, Zunying (Frontiers in Microbiology, 2022)
This study illustrated the texture changes of Shewanella baltica-inoculated Litopenaeus vannamei during refrigerated storage with the exogenous addition of Lactobacillus plantarum SS-128 (SS-128). The group inoculated with SS-128 had an improved texture compared with that inoculated with luxS-mutant group (ΔluxS). Proteomics were conducted to analyze the protein alterations in Litopenaeus vannamei and supernatant, respectively. During storage, many texture-related proteins, including myosin heavy chain and beta-actin, were maintained due to luxS. Some endogenous enzymes related to the energy metabolism and hydrolysis Litopenaeus vannamei were down-regulated. The luxS-induced interaction with Shewanella baltica showed significant changes in the expression of some critical enzymes and pathways. The ATP-dependent zinc metalloprotease FtsH and protease subunit HslV were downregulated, the oxidative phosphorylation and glycosaminoglycan degradation pathways in Shewanella baltica were inhibited, resulting in the slow deterioration of Litopenaeus vannamei. By exploring the mechanism underlying SS-128-led manipulation of the metabolism of spoilage bacteria, we clarified the texture maintenance mechanism of luxS in SS-128, providing theoretical evidence for SS-128 application in food preservation.